SAT0446 Ixekizumab improves patient-reported outcomes in patients with active psoriatic arthritis and previous inadequate response to tumour necrosis factor-inhibitors. (15th June 2017) - Kavanaugh, A; Vender, R; Birt, J; Adams, DH; Benichou, O; Lin, C-Y; Nash, P
Abstract : Background: Ixekizumab (IXE), a monoclonal high affinity antibody that selectively targets interleukin-17A, was superior to placebo (PBO) in achieving clinical responses and improving health related quality of life (HRQoL) for psoriatic arthritis (PsA) patients who were biologic-naïve. 1 Herein, results are presented from a phase 3 trial (SPIRIT-P2; NCT02349295 ) with IXE in patients with active PsA and previous inadequate response to tumor necrosis factor-inhibitors (TNF-i). Objectives: To explore the impact of IXE on patient reported HRQoL outcomes up to 24 weeks (wks) in patients with active PsA. Methods: In this phase 3, multicentre, double-blind study, 363 adult patients with active PsA were randomly assigned in the ratio of 1:1:1 to subcutaneous administration of either 80-mg IXE every 4 wks (Q4W; N=122) or every 2 wks (Q2W; N=123) following a 160-mg starting dose at Wk 0 or PBO (N=118). All patients entering the study had an inadequate response to one or two TNF-i or were intolerant to TNF-i. At baseline and Wk 24, HRQoL was measured by the Short Form-36 Health Survey (SF-36) Physical Component Summary (PCS) and Mental Component Summary (MCS), European Quality of Life 5 Dimensions Visual Analog Scale (EQ-5D VAS), Work Productivity and Activity Impairment-Specific Health Problem (WPAI-SHP; absenteeism; presenteeism, work productivity, and activity impairment), the itch Numeric Rating Scale (NRS), and the Dermatology Life Quality Index (DLQI). Itch NRS, DLQI, and Psoriasis Area Severity Index (PASI) responses were assessed in patients with baseline psoriatic lesion involving ≥3% body surface area (BSA; N=203). Treatment comparisons were made by a mixed model for repeated measures for continuous data and by a logistic regression model for categorical data with missing values imputed by nonresponder imputation. Results: Mean baseline (Wk 0) scores for HRQoL measures indicated impaired physical and mental function, quality of life, and work productivity (Table). At Wk 24, clinical efficacy was shown by 50.6% and 58.1% of IXE-treated patients achieving ACR20 and PASI75 responses, respectively. Patients receiving IXE (Q4W or Q2W) reported significantly greater improvements in SF-36 PCS and MCS, EQ-5D VAS, and WPAI-SHP (presenteeism, work productivity, and activity impairment) than patients treated with PBO (Table; p<.05). For PsA patients with co-morbid psoriasis (≥3% BSA), IXE treatment (Q4W or Q2W) resulted in significantly greater improvements in itch NRS and DLQI than PBO treatment (Table; p<.001). Finally, 51.5% of IXEQ4W patients and 50.0% of IXEQ2W patients reached a DLQI total score of 0 or 1 at Wk 24, which is significantly greater than patients treated with PBO (9.0%, p<.001). Conclusions: In patients with active PsA and previous inadequate response to TNF-i, IXE provided significant improvement through 24 wks in all joint and skin associated HRQoL outcomes, including physical and mental function, quality of life, work productivity, DLQI, and itch. References: Mease P et al. 2017 ARD 76(1):79. Disclosure of Interest: A. Kavanaugh Consultant for: Eli Lilly and Company, R. Vender Grant/research support from: Abbvie, Amgen, Centocor, Dermira, Galderma, GSK, Leo, Eli Lilly and Company, Takeda, Novartis, Merck, Pfizer, Regeneron, Consultant for: Abbvie, Amgen, Janssen, Galderma, GSK, Leo, Eli Lilly and Company, Novartis, Pfizer, Valeant, Actelion, Celgene, Cipher, Palladin, Speakers bureau: Abbvie, Amgen, Janssen, Galderma, GSK, Leo, Eli Lilly and Company, Novartis, Pfizer, Valeant, Actelion, Celgene, Cipher, Palladin, J. Birt Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, D. Adams Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, O. Benichou Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, C.-Y. Lin Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, P. Nash Grant/research support from: AbbVie, Amgen, BMS, Celgene, Eli Lilly and Company, Hospira, MSD, Pfizer, Janssen, UCB, Novartis, Roche, Sanofi, Consultant for: AbbVie, Amgen, BMS, Celgene, Eli Lilly and Company, Hospira, MSD, Pfizer, Janssen, UCB, Novartis, Roche; Sanofi, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Eli Lilly and Company, Hospira, MSD, Pfizer, Janssen, UCB, Novartis, Roche, Sanofi